Objective Value of the Apparent Diffusion Coefficient (ADC) Map from Ultrahigh b-value Diffusion-weighted Imaging (DWI) in 3T MRI could be a Non-invasive Specific Biomarker for Prostate Cancer - Zhang, Kun; Zhang, Chen; Chen, Zhengming; Zhang, Yun; Dong, Zhe; Hu, Yingying; Wang, Meifeng; Fu, Yonggui; Ye, Huiyi; Shen, Yanguang (Current Medical Imaging, 2024)
Objective:This article aims to explore the ADC value of ultrahigh b-value DWI and the diagnostic cutoff point in prostate cancer.Methods:A total of 78 patients were included in this study. T2 weighted imaging (T2WI), conventional diffusion-weighted imaging (DWI) (1000 s/mm2), and DWI with ultrahigh b-values of 2000 s/mm2 and 3000 s/mm2 were performed in each patient. With reference biopsy as the gold standard, the apparent diffusion coefficient (ADC)s of each b-value DWI image were analyzed. According to different b-value receiver operating characteristic (ROC) curves, the ADC diagnostic cutoff point for prostate cancer was determined.Results:A total of 154 lesions were identified as prostate cancer. The ADC values for conventional DWI and ultrahigh b-value DWI with 2000 s/mm2 and 3000 s/mm2 were 1.097×10-3 mm2/s (1.040-1.153), 0.809×10-3 mm2/s (0.766-0.851) and 0.622×10-3 mm2/s (0.591-0.652), respectively, in the peripheral zone and 1.085×10-3 mm2/s (1.022-1.147), 0.815×10-3 mm2/s (0.770-0.861) and 0.651×10-3 mm2/s (0.617-0.685) in the transition zone. The area under the curve (AUC)s of the ADC values from ultrahigh b-value DWI (2000 s/mm2 and 3000 s/mm2) were 0.824 and 0.852 in the peripheral zone and 0.905 for the ADC values from ultrahigh b-value DWI (3000 s/mm2) in the transition zone. In the peripheral zone, the ADC diagnostic cutoff values for prostate cancer were 0.75×10-3 mm2/s and 0.685×10-3 mm2/s in DWI at 2000 s/mm2 and 3000 s/mm2, respectively, and the diagnosis of transition zone cancer was 0.8×10-3 mm2/s and 0.634×10-3 mm2/s, respectively.Conclusion:The ADC values from ultrahigh b-value DWI demonstrated better consistency and diagnostic efficacy in the diagnosis of prostate cancer.
Keywords: Diffusion coefficient